Circulating adipokine concentrations and the risk of venous thromboembolism: A Mendelian randomization and mediation analysis - Xiao, Weizhong; Li, Jian; Feng, Tianyuyi; Jin, Long (Frontiers in Genetics, 2023)
Background Previous observational studies have suggested that circulating adipokine concentrations are related to a greater risk of venous thromboembolism (VTE). However, it remained unclear whether these observations reflect causality. Objective This study aimed to investigate the causal relationship between circulating adipokine concentrations (including adiponectin, leptin, PAI-1, MCP-1, leptin receptor and RETN) and the risk of VTE and its subtypes (DVT, PE), as well as to determine whether circulating adipokine concentrations are a mediator of venous thromboembolic events in obese patients. Methods We used Mendelian randomization (MR) analyses to determine the effects of body mass index (BMI), adiponectin, leptin, PAI-1, MCP-1, leptin receptor and RETN levels on VTE, DVT, and PE in a cohort of 11,288 VTE cases, 5,632 DVT cases, 5,130 PE cases and 254,771 controls. We then assessed the proportion of the effect of obesity on VTE, DVT and PE explained by circulating leptin levels. Result Genetically predicted higher BMI was related to increased VTE(OR=1.45, p＜0.001) , DVT(OR=1.63, p＜0.001) and PE(OR=1.37, p＜0.001) risk, and higher circulating leptin levels increase odds of VTE (OR=1.96, q＜0.001) , DVT (OR=2.52, q＜0.001) and PE (OR=2.26, q=0.005). In addition, we found that the casual effect between elevated serum adiponectin and decreased risk of VTE (OR=0.85, p=0.013, q=0.053) and PE (OR=0.81, p=0.032, q=0.083) and between MCP-1 and reduced risk of VTE (OR=0.88, p=0.048, q=0.143) is no longer significant after FDR adjustment. In MR mediation analysis, the mediation effect of circulating leptin levels in the causal pathway from BMI to PE was estimated to be 1.28 (0.95-1.71, p=0.10), accounting for 39.14% of the total effect. Conclusion Circulating leptin level was a risk factor for VTE, DVT and PE, but it might be a potential mediator of BMI on the risk of PE and thus interventions on circulating leptin levels in obesity might reduce the risk of PE. Adiponectin is a potential protective factor for both VTE and PE.